The Effect of Toxic Workplace Environment on Employee Performance Mediated by Employee Engagement and Work Stress Among F&B Employees in Jakarta - Shelvy Kurniawan; Farras Ammar Bamumin; Kevin Novaldi Kusnandar (Business Economic, Communication, and Social Sciences Journal (BECOSS), 2023)
Employee engagement and high work stress often become obstacles for MSMEs to produce good employee performance. One of the problems in human resources that often occur is a toxic workplace environment. The purpose of this study was to determine the effect of a toxic workplace environment on employee performance mediated by work stress and employee engagement among F&B MSMEs employees in Jakarta. This research uses quantitative research methods. Questionnaires were distributed to F&B MSMEs employees in Jakarta and the data obtained was processed using SmartPLS. This study has a respondent of 400 respondents. The results showed that there was a positive effect between a toxic workplace environment on work stress, a negative effect between a toxic workplace environment on employee engagement, a negative effect between work stress and employee performance, a positive effect between employee engagement and employee performance, a non-significant negative effect of a toxic workplace environment on employee performance, there is a significant negative effect of a toxic workplace environment mediated by work stress on employee performance, and there is a significant negative effect of a toxic workplace environment mediated by employee engagement on employee performance.